INTERDISCIPLINARY APPROACH IN THE LEARNING OF SOCIAL SCIENCE - Zahroh, Nur Lailatus; Sari, Ulfi Andrian; Nulinnaja, Ratna (Proceeding of International Conference on Islamic Education (ICIED); Vol 3 No 1 (2018): Proceeding of International Conference on Islamic Education (ICIED), 2018)
Abstract. The interdisciplinary approach can be implemented through an integrated learning. Social Science learning separately raises several problems, for instance students have a low mastery of Social Science concepts and difficulties in linking among social science concepts. This study aims to improve the mastery of the concept of Social Sciences by students with an interdisciplinary approach in Social Science learning. This is a research and development (R & D) research. Data collection techniques use observation, interview and documentation. The results of this study show that Social Science learning with an interdisciplinary approach can improve the mastery of the concept by students with very good categories. It is suggested that the interdisciplinary approach can be applied in Social Science lectures.